Changes in choroidal thickness and retinal activity with a myopia control contact lens - Amorim-de-Sousa, Ana (2023)
Purpose: The axial elongation in myopia is associated with some structural and functional retinal changes. The purpose of this study was to investigate the effect of a contact lens (CL) intended for myopia control on the choroidal thickness (ChT) and the retinal electrical response. Methods: Ten myopic eyes (10 subjects, 18–35 years of age) with spherical equivalents from −0.75 to −6.00 diopters (D) were enrolled. The ChT at different eccentricities (3 mm temporal, 1.5 mm temporal, sub-foveal ChT, 1.5 mm nasal, and 3 mm nasal), the photopic 3.0 b-wave of ffERG and the PERG were recorded and compared with two material-matched contact lenses following 30 min of wear: a single-vision CL (SV) and a radial power gradient CL with +1.50 D addition (PG). Results: Compared with the SV, the PG increased the ChT at all eccentricities, with statistically significant differences at 3.0 mm temporal (10.30 ± 11.51 µm, p = 0.020), in sub-foveal ChT (17.00 ± 20.01 µm, p = 0.025), and at 1.5 mm nasal (10.70 ± 14.50 µm, p = 0.044). The PG decreased significantly the SV amplitude of the ffERG photopic b-wave (11.80 (30.55) µV, p = 0.047), N35-P50 (0.90 (0.96) µV, p = 0.017), and P50-N95 (0.46 (2.50) µV, p = 0.047). The amplitude of the a-wave was negatively correlated with the ChT at 3.0T (r = −0.606, p = 0.038) and 1.5T (r = −0.748, p = 0.013), and the amplitude of the b-wave showed a negative correlation with the ChT at 1.5T (r = −0.693, p = 0.026). Conclusions: The PG increased the ChT in a similar magnitude observed in previous studies. These CLs attenuated the amplitude of the retinal response, possibly due to the combined effect of the induced peripheral defocus high-order aberrations impacting the central retinal image. The decrease in the response of bipolar and ganglion cells suggests a potential retrograde feedback signaling effect from the inner to outer retinal layers observed in previous studies.